Multicultural Politics of Canada (Journal of Philosophy Culture and Political Science, 2018)
The policy of multiculturalism is an important issue in contemporary international relations. The policy of multiculturalism caused by migration processes. The idea of multiculturalism emerged in Canada as the official state policy as a program of nation building. Today, multiculturalism is official state policy. Multiculturalism in Canada has a legislated strategy of cultural policy. In July 1988, Canada became the first country in the world that has adopted the Act of multiculturalism. According to it multiculturalism is a fundamental characteristic of canadian society. The purpose of this policy is the preservation and development of different cultures.Key words: Canada, politics, culture, migration, ethnic groups, foreign policy.